CALMODULIN-BINDING TRANSCRIPTION ACTIVATOR 6: A Key Regulator of Na(+) Homeostasis during Germination - Shkolnik, Doron (Plant Physiol, 2019)
Salinity impairs seed germination and seedling establishment. We investigated the role of Arabidopsis (Arabidopsis thaliana) CALMODULIN-BINDING TRANSCRIPTION ACTIVATOR 6 (CAMTA6) in salinity stress responses during early germination. Compared with the wild type, the camta6-4 and camta6-5 mutants were more tolerant to NaCl and abscisic acid (ABA) and accumulated less Na(+). In contrast, 4- to 11-d-old camta6 seedlings were more sensitive to NaCl. In camta6, expression of HIGH-AFFINITY K(+) TRANSPORTER1 (AtHKT1;1), encoding an Na(+)/K(+) transporter, was restricted to the radicles and was not enhanced by NaCl or ABA. During germination, the camta6 hkt1 double mutant was as sensitive as the wild type and hkt1 to NaCl, suggesting that HKT1;1 is crucial for the salt tolerance of camta6. An ABA response element in the HKT1;1 promoter was found to be indispensable for the enhanced expression of the gene in response to NaCl and to ABA. Transcriptome analysis of the wild type and camta6-5 with and without salt treatment revealed 1,020 up-regulated and 1,467 down-regulated salt-responsive genes in the wild type. Among these, 638 up-regulated and 1,242 down-regulated genes were classified as CAMTA6-dependent. Expression of several known salt stress-associated genes, including SALT OVERLY SENSITIVE1 and Na(+)/H(+) ANTIPORTER, was impaired in camta6 mutants. Bioinformatics analysis of the 5′ upstream sequences of the salt-responsive CAMTA6-dependent up-regulated genes revealed the CACGTGTC motif as the most prominent element, representing an ABA response element and a potential CAMTA-binding site. We suggest that CAMTA6 regulates, directly or indirectly, the expression of most of the salt-responsive genes in germinating seeds, including genes that are crucial for Na(+) homeostasis and salt stress tolerance.